2009
DOI: 10.1016/s1726-4901(09)70424-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intradural Hemangiopericytoma With Intramedullary Invasion

Abstract: Hemangiopericytoma (HPC) is a rare tumor of the central nervous system and is usually found intracranially. Intraspinal HPCs are very rare and mostly involve the extradural bony structures. Primary intradural HPC has only been reported in 10 cases, all of which occurred in the extramedullary region. Intramedullary invasion has never been reported. Here, we describe a case of primary intradural HPC of the thoracic spine that presented initially with paresthesia and paraplegia of both legs. Magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…3,49 However, some other surgeons have claimed that total resection does not always provide a clinical benefit for patients with HPCs. 23,27 In our results, we also found that total resection did not represent a statistically significant survival or recurrence-free benefit. Thus, total resection in highrisk patients may not be necessary for intraspinal HPCs, especially those hard to remove totally, such as types IB and III.…”
Section: Surgerysupporting
confidence: 52%
See 1 more Smart Citation
“…3,49 However, some other surgeons have claimed that total resection does not always provide a clinical benefit for patients with HPCs. 23,27 In our results, we also found that total resection did not represent a statistically significant survival or recurrence-free benefit. Thus, total resection in highrisk patients may not be necessary for intraspinal HPCs, especially those hard to remove totally, such as types IB and III.…”
Section: Surgerysupporting
confidence: 52%
“…37,38 Some spinal schwannomas showed a fluid signal intensity on T2-weighted MRI and rim enhancements on a contrast-enhanced T1-weighted MRI, 39 whereas HPCs commonly have an isointense signal and a homogeneously enhanced image on an MRI. 25,27,35 The subtype of IIB needed to be differentiated from ependymomas and hemangioblastomas. Some type IB and III tumors have an absorptive erosion on the vertebral body, appendix, or plate, which can be characteristic and assist in the diagnosis.…”
Section: Hemangiopericytomas In the Spinementioning
confidence: 99%
“…The first intradural case was reported in 1961 by Kruse [11]. Since then, 23 cases have been reported, including our four present cases [4][5][6][7][8][9][10][11][12][13][14]. The occurrence of HPCs has been reported throughout the cervical, thoracic and lumbar spine, but the cervicothoracic region appears to have the greatest prevalence ( Table 2).…”
Section: Discussionmentioning
confidence: 91%
“…Cases of spinal HPCs are extremely rare and are most often intradural. There have been only 19 reported cases of intradural tumors, most being extramedullary [4][5][6][7][8][9][10][11][12][13][14]. Only two prior case reports have been documented to have intramedullary involvement [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…HPCs in the spine may involve the structures of the vertebra and the spinal canal, including the extradural and intradural space. Our search of the literature showed that 140 cases of HPC in the spine had been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(49)(50)(51)(52)(53)(54)(55)(56), and 64 cases were extradural (2, 4-6, 8-10, 15, 20-22, 24, 25, 27, 28, 31, 32, 34, 35, 37, 40-42, 44-46, 49, 51, 53-55) (Table I). Here we present a case of primary HPC invasion in the cervicothoracic spine, as well as presenting a review of the literature.…”
Section: Introductionmentioning
confidence: 99%